Characterizations of the first flush in storm water runoff from an urban roadway - Lee, B C (Environmental technology, 2005)
Storm water runoff from urban roadways contains anthropogenic pollutants, which are mainly generated from traffic-related activities. The purpose of this study was to evaluate the characteristics of pollutants from the roadway runoff as well as first flush effects. Storm water runoff was sampled during five storm events from the experimental site in Otsu, Shiga, Japan. From the hydrographs and pollutographs for the roadway runoff, the concentration of pollutants increased with increasing runoff flow in the low flow rate event, but did not significantly increase in the high flow rate event. Moreover, according to the analysis of cumulative pollutant mass versus runoff volume curves from five storm events, the first 50% of the runoff volume transported 62% of TOC and Mo, 60% of SS, 59% of Fe, Mn and Cu, 58% of Ni, 57% of Cd and Pb, 56% of Al, 55% of Zn, and 54% of Cr, as the mean values. The first 30% and 80% of the runoff volume also transported 34-43% mass of the pollutants and 82-88% mass of the pollutants, respectively. This study for storm water runoff may also provide useful information to correctly design treatment facilities, such as detention tanks and ponds, filtration and adsorption systems